DIGITAL RUPTURES: AI-GENERATED ACTIVISM, STATE REPRESSION, AND THE POLITICS OF DISSENT IN KENYA - Mwaura, Job (AoIR Selected Papers of Internet Research, 2026)
The June 2024 Gen Z protests in Kenya marked a turning point in AI-generated activism, as digital tools became central to political resistance. Following state-led crackdowns, activists retreated online, deploying AI-generated satire, deepfake videos, and synthetic media to challenge government narratives. In response, the Kenyan government escalated AI-driven surveillance, censorship, and metadata tracking, leading to abductions, disappearances, and intensified digital repression. This paper examines how AI functions as both an instrument of political resistance and a tool of state control, creating a contested digital battleground. Using digital ethnography and document analysis, the study situates Kenya’s evolving civic space within broader trends of algorithmic governance and digital authoritarianism. Drawing on Feldstein’s (2023) framework of digital repression and Nyamnjoh’s (2023) critique of digital-human fluidity, it explores the shifting state-citizen relationship, where AI empowers both dissent and control. These findings highlight the escalating technological arms race between activists and the state, shaping Kenya’s future of digital governance and political expression.